Oxidative refolding of rPA in l‐ArgHCl and in ionic liquids: A correlation between hydrophobicity, salt effects, and refolding yield. Issue 11 (November 2014) - Tischer, Alexander; Lilie, Hauke; Auton, Matthew; Lange, Christian
ABSTRACT The ionic liquid 1‐ethyl‐3‐methyl imidazolium chloride (EMIM Cl) and the amino acid l‐arginine hydrochloride (l‐ArgHCl) have been successfully used to improve the yield of oxidative refolding for various proteins. However, the molecular mechanisms behind the actions of such solvent additives—especially of ionic liquids—are still not well understood. To analyze these mechanisms, we have determined the transfer free energies from water into ionic liquid solutions of proteinogenic amino acids and of diketopiperazine as peptide bond analogue. For EMIM Cl and 1‐ethyl‐3‐methyl imidazolium diethyl phosphate, which had a suppressive effect on protein refolding, as well as for l‐ArgHCl favorable interactions with amino acid side chains, but no favorable interactions with the peptide backbone could be observed. A quantitative analysis of other ionic liquids together with their already published effects on protein refolding showed that only solvent additives within a certain range of hydrophobicity, chaotropicity and kosmotropicity were effective for the refolding of recombinant plasminogen activator. © 2014 Wiley Periodicals, Inc. Biopolymers 101: 1129–1140, 2014.